Ecofriendly Method of Coir Retting and Pith Utilization Using Bioinoculants-‘‘Coirret’’ and ‘‘Pithplus’’ - Anita Das Ravindranath (International Coconut Community, 2008)
Coir fibre and coir pith are byproducts of the coconut which are a renewable biomass. The coir fibre is used for the manufacture of natural fibre products such as yarn, brushes, brooms, door mats and floor covering products and the pith has potential for use as plant nutrient source. Biotechnology has been applied to improve upon the conventional drudgery prone, non hygienic and polluting methods to extract coir fibre from coconut husks. Technology has also been developed to convert pith into a soil conditioner and potting medium for use in agriculture and horticulture. This paper presents data on “Coirret” a bacterial consortium for enhancement of retting process of coconut husks / fibre bales and “Pithplus” a white rot fungal biomass developed for biodegradation of lignin in coir pith for economic utilisation.